IMPLEMENTASI PENGEMBANGAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 1 SITUBONDO - Raudatul Jannah Firdausiyah (UNISAN JURNAL, 2024)
This study plans to analyze the execution of learning assessment of Islamic Strict Training (PAI) and Qualities in the 2013 Educational program at SMP Negeri 1 Situbondo. The examination techniques utilized incorporate perception, meetings, and report investigation. The information gathered incorporates the most common way of learning assessment, assessment instruments, assessment results, as well as the perspectives on instructors and understudies on the assessment. The consequences of the examination show that SMP Negeri 1 Situbondo has completed a decent assessment of PAI and Qualities learning. Educators utilize the perception technique to notice understudies’ advancement in grasping Islamic religion and applying moral qualities. The assessment instruments utilized incorporate composed tests, tasks, and participatory perception. The assessment results show an expansion in understudy figuring out, use of moral qualities, as well as the advancement of resilience, sympathy, and viable correspondence. Moreover, educators additionally break down assessment results and utilize the information to make upgrades in the growing experience. They work together between educators in planning significant and viable assessment instruments. What’s more, understudies and guardians are likewise engaged with learning assessment through meetings and input gave.